(untitled) (Bangladesh Journal of Agriculture, 2022)
Flash flood is the most commonly occurring water related disaster in the haor area of Bangladesh. It’s occurs during the pre-monsoon season (March-April-May). The haor area is very susceptible to climatic risk and prone to early flash flood in consecutive year. In response, the government of Bangladesh has initiated a number of institutional interventions through development plans to better support sustainable adaptation. A study was carried out to assess the climate change risks and adaptation of indigenous farming practices of dekhar haor in Sunamganj district. Data were collected through direct interview from randomly selected 96 farmers, 4 Focus Group Discussion and 10 Key Informant Interviews during September 2019 to January 2020. It was found that the most potential climatic hazards of the study area were flash flood, thunderstorm, hailstorm and drought. The data related to agricultural adaptation strategies to climate change indicated that the majority (54.2%) farmers had medium adaptation and 45.8% low adaptation and no farmers were found with high adaptation. Climatic risks at different agricultural sectors such as crop protection, community protection, fisheries, livestock and risk of drought were assessed through comparative analysis of climatic hazards, vulnerability to climate change and adaptation capacity. Bangladesh J. Agri. 2022, 47(1): 39-65